The Oasis of Bukhara, Volume 2: Archaeological Pluridisciplinary Activities and Historical Study - Rante, Rocco, author.
1 online resource.
Keywords: In Archaeological Pluridisciplinary Activities and Historical Study, volume 2 of The Oasis of Bukhara, Rocco Rante, Florian Schwarz and Luigi Tronca engage in a strong, pluridisciplinary collaboration and use an innovative approach to offer a new contribution to the history of the oasis of Bukhara from the end of the last millennium BCE to the end of the medieval era. Referencing archaeological, historical and sociological data, the book revisits the history of this Central Asian region, giving the reader, specialist and general reader a detailed description of the political and socio-economical features that characterized the oasis during this long chronological span.